E-Arsip Surat Tugas Pada Kantor Badan Pusat Statistik (BPS) Kabupaten Langkat Berbasis Website - Sujacka Retno, Rozzi Kesuma Dinata, Aina Rahmadani (Jurnal Elektronika dan Teknologi Informasi, 2023)
BPS (Badan Pusat Statistik) is a non-ministerial government agency that is directly responsible to the President. The BPS office in Langkat Regency provides statistical data and information needed for sectoral and cross-sectoral planning and development. At the Langkat Regency BPS Office, the assignment letter management and archiving system is still carried out manually, by using a file cabinet. This manual data collection can make it difficult for officers to manage related to archiving letters and preparing reports so that this can hinder the performance of BPS officers. This research aims to overcome these problems by creating an e-archive system that aims to optimize the performance of officers at the Langkat Regency BPS office. The system was built using PHP and MySQL database.